Albania - Urban Growth, Migration and Poverty Reduction : A Poverty Assessment - World Bank (Washington, DC, 2012)
This sector report claims that in the three years between 2002 and 2005 alone, almost 235,000 people have moved out of poverty in Albania. Strong economic growth and large inflow of remittances are at the center of this impressive achievement. However, low productivity of predominantly small family farms has put a drag on rural growth prospects. Moreover, Ndihma Ekonomike (NE) program, the means-tested income support program is small in scale, and has a low coverage so that it has had only a modest impact on poverty reduction. As a result of these developments, the poor are mostly rural residents, low skilled (measured as years of schooling completed) and large families. The main conclusion of this report is that as Albania looks ahead it faces the challenges of consolidating and sustaining these improvements in living conditions and narrow the widening rural and urban differences. To tackle these challenges, Albania needs to maintain the high growth path, raise rural productivity and improve the targeting performance of its NE program